Event history analysis of the duration of online public opinions regarding major health emergencies - Liu, Xiaoyan; Zhao, Jiarui; Liu, Ran; Liu, Kai (Frontiers in Psychology, 2022)
Based on event history analysis, this study examined the survival distribution of the duration of online public opinions related to major health emergencies and its influencing factors. We analyzed the data of such emergencies (N = 125)that took place in China duringa period of ten years (2012-2021). The results of the Kaplan-Meier method and Cox proportional hazards regression analysis showed that the average duration of online public opinions regarding health emergencies is 43 days, and the median is 19 days, which dispels the myth of the “Seven-day Law of Propagation”. Furthermore, the duration of online public opinions can be divided into three stages: the rapid decline stage (0-50 days), the slowdown stage (51-200 days), and the disappearing stage (after 200 days). In addition, the type of event, and the volume of both social media discussion and traditional media coverageall had significant impacts on the duration. Our findings provide practical implications for the carrying out of targeted and stage-based governance of public opinions.